Quantitative assessment of the individual contribution of climate and human factors to desertification in northwest China using net primary productivity as an indicator. (January 2015) - Zhou, Wei; Gang, Chengcheng; Zhou, Fuchun; Li, Jianlong; Dong, Xiaogang; Zhao, Chengzhang
Highlights: NPP was used to assess the relative role of the driving factors in desertification. Desertification expanded in 55.8% of the entire study area. Human activities promote desertification expansion, climate benefits the reversion. Contributions of the two factors varied greatly in six provinces. Environmental protect programs are beneficial to the desertification control. Abstract: An accurate quantitative assessment of the relative roles of climate change and human activities in desertification is significant to understand the driving mechanisms deeply and control desertification development. In this study, we selected net primary productivity (NPP) as an indicator to discriminate the relative roles of climate and human factors in desertification during 2001–2010 in northwest China. The potential NPP and the difference between potential and actual NPPs were used to represent the impacts of climate change and human activities on desertification. Desertification expanded on 55.8% of the study area, within which 70.3% of the desertification expansion was caused by human activities compared with only 21.7% induced by climate change. On the contrary, 42.1% of desertification reversion was caused by human activities and 48.4% resulted from climate changes. The NPP variation also could be calculated to assess the relative roles and showed that 69% of NPP decrease was caused by human impacts compared with 15.2% induced by climate change. By contrast, 23.9% of NPP increase was caused by climate change, whereas 54% resulted from human activities. In addition, the relative roles of two factors possessed great spatial heterogeneity in six provinces. We developed three propositions. First, the desertification expansion was dominated by human activities, whereas desertification reversion was dominated by climate change, as typified by Xinjiang, Qinghai, and Gansu. Second, both desertification expansion and reversion were induced by human activities, as typified by the west of Inner Mongolia and Shaanxi. Third, climate change dominated the desertification expansion in Ningxia province.